FOOD SERVED AMONG THE INMATES IN ‘PRESCRIBED PRISONS’: AN ANALYSIS IN THE BACKGROUND OF HUMAN RIGHT NORMS - Dr. Banamali Barik (International Journal of Legal Developments & Allied Issues, 2018)
Food is a basic requirement of human life. Article-11 of International Covenant on Economic, Social and Cultural Rights, recognizes the right of everyone to an adequate food and drinking water. Right to food (or absence of hunger) and nutrition is an integral part of right to life mentioned in Article 21 of the Constitution. Rule-4, of Standard Minimum Rules for the Treatment of prisoners states that every prisoner shall be provided by the administration at the usual hours with food of nutritional value adequate for health and strength, of wholesome quality and well prepared and served. Model Prison Manual (2003), deals with preparation, distribution and quality of food provided to the prisoners and an average man requires approximately 2,000 to 2,400 calories a day. According to medical science, an average man needs at least 2000 calories a day. Rule-983 & 993 of Orissa Jail Manual, 1942, states that “All prisoners shall have three meals a day. It is of great importance that the dietary should be varied as much as possible”. However, the prison administration and management have been subjected to criticism by courts, prisoners and public for not maintaining the basic minimum standards of human dignity, and for the poor living condition of inmates in place of human confinement like prison. The paper examines the ‘food served’ by the prison administration at the usual hours and the adequacy of nutritional value for health and strength of the prisoners in the light of human right norms.